Research Progress on the Ability of Astragaloside IV to Protect the Brain Against Ischemia-Reperfusion Injury - Kang, Xianhui; Su, Shuyue; Hong, Wandong; Geng, Wujun; Tang, Hongli (Frontiers in Neuroscience, 2021)
Stroke, a disease with a sudden onset and high morbidity and mortality rates, is difficult to treat in the clinic. Traditional Chinese medicine has become increasingly widely used in clinical practice. Modern pharmacological studies have found that Radix Astragali has a variety of medicinal properties, i.e., immunoregulatory, antioxidative, anti-cancer, anti-diabetes, myocardial protective, hepatoprotective and antiviral functions. This article reviews the protective effect and mechanism of astragaloside IV, which is extracted from Radix Astragali, on stroke, discusses the cerebroprotective effect of astragaloside IV against ischemia-reperfusion-related complications, offers insight into research prospects, and expands the idea of integrating traditional Chinese and Western medicine treatment strategies and drugs to provide a theoretical reference for the clinical treatment of cerebral ischemia-reperfusion injury and the improvement of stroke prognosis.